PARP12 is required for mitochondrial function maintenance in thermogenic adipocytes. (31st December 2022) - Hu, Fan; Li, Chang; Ye, Yafen; Lu, Xuhong; Alimujiang, Miriayi; Bai, Ningning; Sun, Jingjing; Ma, Xiaojing; Li, Xiaohua; Yang, Ying
ABSTRACT: PARP12 is a member of poly-ADP-ribosyl polymerase (PARPs), which has been characterized for its antiviral function. Yet its physiological implication in adipocytes remains unknown. Here, we report a central function of PARP12 in thermogenic adipocytes. We show that PARP12 is highly expressed in brown adipose tissue and is mainly localized to the mitochondria. Knockdown of PARP12 in vitro reduced UCP1 expression. In parallel, the deficiency of PARP12 reduced mitochondrial respiration in adipocytes, while overexpression of PARP12 reversed these effects.